Sensitive agents under group pressure form fewer opinion clusters. (1st June 2022) - Huang, Changwei; Cai, Huasheng; Han, Wenchen
Abstract: The number of opinion clusters is the main focus of opinion dynamics. Different methods have been proposed to help agents form fewer opinion clusters or achieve consensus. In this study, sensitive agents suffering the group pressure are introduced into the Hegselmann-Krause opinion model, where other agents are insensitive and without the group pressure. The introduction of sensitive agents provides more chances for cluster merging, forming fewer clusters, and even reaching consensus. The sensitive factor plays a dominant role in opinion consensus: a large value for the group pressure becomes the public opinion, small value makes the group pressure concentrate on the agent's own opinion, and medium one causes a nonlocal one to greatly forge consensus. The group pressure significance tunes the proportion group pressure felt by sensitive agents and forms fewer clusters together with the sensitive factor. Surprisingly, the ratio of sensitive agents shows almost no difference.